Percepções e condutas maternas quanto à alimentação de crianças com múltiplas deficiências e problemas alimentares - Botelho, Rafael Lacerda (2017)
Introduction: Multiple disabilities are a serious clinical condition, since there is a sum of different alterations affecting the subject’s development. In cases of physical deficiency composing the pathological multiplicity, alimentation represents one of the most disturbed aspects, besides language itself and even cognition. Studies of the eating scene in these cases are still limited, and those orientated to the maternal side of the scene, are even more restricted. Studies of this type are justified because they bring to the discussion subjective content, which can clarify certain maternal behaviors, making clinical decisions more effective, especially those that refer to family consulting. Objective: To identify maternal behaviors and perceptions in feeding scenes with their children with Multiple Disabilities. Method: we used the Discourse of the Collective Subject technique, a methodology that consisted of the elaboration of a synthesis discourse, based on the statements of a group of ten mothers, in clinical interviews, on the development of the feeding of their children, with multiple deficiency, especially with alterations in the motor aspect, which in almost all cases, determined the insertion of alternative feeding or food retention in the pasty texture. Results: the mothers report desire and pleasure in breastfeeding, as well as the impact of abrupt weaning due to the early hospitalization of their children; they also report how the serious clinical picture that presents itself is for the dismantling of the eating scene and the consequent absence of these subjects in the scenes of the familiar meals, privileged space of interaction. Finally, they report their attempts to rescue opportunities for interaction even in disturbed food scenes. Conclusion: the study of the maternal attitudes and feelings towards eating scenes provides important data that should guide any clinical project of family counseling in the case of subjects with disabilities